PELATIHAN INTEGRASI DIGITALISASI DAN KOMUNIKASI BISNIS BAGI PELAKU UMKM IKATAN PENGUSAHA MUSLIMAH INDONESIA (IPEMI) KOTA SEMARANG - Hendriyani, Ida; Zusrony, Edwin; Anzie, Luthfy Purnanta; Santoso, Agustinus Budi; Widyaningsih, Dewi (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
The government and stakeholders are concentrating on digital business integration within the SME sector to enhance economic independence. Training for SME partners within the IPEMI community in Semarang city, informed by preliminary surveys and interviews concerning competency development requirements. The swift digital business transformation following the COVID-19 epidemic has altered business operations. The program comprises three sessions: adopting Google Trends in small and medium-sized enterprises, integrating digital business via websites, and enhancing product branding through business communications. Fourteen members of IPEMI from UKM participated in this service activity in Semarang. Consequently, participants might improve their proficiency, achieving post-test scores over 80%.